2017
DOI: 10.1021/jacs.7b00924
|View full text |Cite
|
Sign up to set email alerts
|

Cleaving Dihydrogen with Tetra(o-tolyl)diborane(4)

Abstract: Tetra(o-tolyl)diborane(4), 1, was synthesized and characterized experimentally as well as theoretically by density functional theory (DFT) calculations. Exposure of 1 to H (1 bar) at room temperature afforded the corresponding di(o-tolyl)hydroborane through cleavage of the H-H and B-B bonds. DFT calculations suggested a diarylboryl anion character for the transition state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
71
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 50 publications
6
71
0
4
Order By: Relevance
“…[13] To investigate the electronic structure of 2 and 3,D FT calculations were conducted at the M06-2X/6-31G(d) level of theory.The main contribution to the HOMO of 2 and 3 is the p-orbital on two boron atoms (Figure 3a nd Figure S20). [7] These results of calculations supported the nucleophilicity of p-orbitals on two boron atoms like alkenes.NBO analysis revealed the B = Bd ouble-bond character in 2 and 3 with WBI values of 1.65 and 1.56, which are significantly larger than that of 1 (0.96) (Table S3). These two orbitals would originate from the LUMO and HOMO of neutral diborane(4) 1.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…[13] To investigate the electronic structure of 2 and 3,D FT calculations were conducted at the M06-2X/6-31G(d) level of theory.The main contribution to the HOMO of 2 and 3 is the p-orbital on two boron atoms (Figure 3a nd Figure S20). [7] These results of calculations supported the nucleophilicity of p-orbitals on two boron atoms like alkenes.NBO analysis revealed the B = Bd ouble-bond character in 2 and 3 with WBI values of 1.65 and 1.56, which are significantly larger than that of 1 (0.96) (Table S3). These two orbitals would originate from the LUMO and HOMO of neutral diborane(4) 1.…”
supporting
confidence: 53%
“…[9] DFT calculations suggested the high reactivity of 1 toward these molecules would originate from al ow-lying LUMO consisting of two vacant p-orbitals on two boron atoms and ar eactive BÀBs ingle bond contributing to the HOMO. [7] Considering as imple structure and scalable synthesis of 1,o ne can expect that the dianion of 1 would have av ariety of reactivity in comparison to other diborane (4) dianions.H erein, we describe the synthesis of tetraaryldiborane(4) dianions by reduction of 1,adetailed study on their photophysical and electrochemical properties,and their reactivity as two equivalents of diarylboryl anion, toward electrophiles. Thelithium salt of diborane(4) dianion 2 was obtained as adark-red solid in 98 %yield by the two-electron reduction of tetra(o-tolyl)diborane(4) 1 with metallic lithium in toluene/ THF (Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Even though it can be expected that diboranes (4) without the stabilization from heteroatoms should exhibit higher reactivity than heteroatom-stabilized diboranes (4), examples for the reactivity of such diboranes(4) remain limited. [14] Herein, we report that the reaction between 1 and CO affords 2-boraindane and boroxine,leading to concomitant complete cleavage of the C Ot riple bond and aC (sp 3 ) À Hb ond, while the reaction with isocyanides furnishes isocyanide-coordinated boraalkenes or the C(sp 2 ) À Hb ond cleaved products. [14] Herein, we report that the reaction between 1 and CO affords 2-boraindane and boroxine,leading to concomitant complete cleavage of the C Ot riple bond and aC (sp 3 ) À Hb ond, while the reaction with isocyanides furnishes isocyanide-coordinated boraalkenes or the C(sp 2 ) À Hb ond cleaved products.…”
mentioning
confidence: 93%
“…Meanwhile, Yamashita and co-workers showed that exposure of tetra(o-tolyl)diborane(4) 2 with H 2 gas resulted in simultaneous cleavage of HH and BB bonds to afford the corresponding di(o-tolyl)hydroborane under mild conditions. 5 They stated that hydrogenation proceeded when the CBBC torsion angle is minimized and thereby the lowest unoccupied molecular orbital (LUMO) is most stabilized. This assures that the merging of the two vacant boron p orbitals plays an important role for furnishing such reactivity.…”
mentioning
confidence: 99%